Exploring Teachers’ Perception About Rosetta Stone As A Reading Teaching Media for Young Learner - Faradilla, Annisa; Daulay, Sholihatul Hamidah (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
In the industrial revolution 4.0, education can no longer be separated from technology. Technology affects all aspects of education including students. Technology affects how they see, hear, speak, and communicate. This study aims to find out how the teacher perceptions of Rosetta Stone software as reading teaching media at the elementary level. The subjects in this study were 2 English teachers and 12 students in grade 1 elementary level. This study used observation and open interviews so that respondents can answer interview questions clearly and completely according to their portions. The results showed that the use of Rosetta stone software as reading teaching media gives positive responses: (1) increasing students’ attention in reading, (2) increasing students’ motivation in reading, and (3) increasing the effectiveness of learning.